Oral administration of VDAC1-derived small molecule peptides increases circulating testosterone levels in male rats - Martinez–Arguelles, Daniel B.; Nedow, Jennifer W.; Gukasyan, Hovhannes J.; Papadopoulos, Vassilios (Frontiers in Endocrinology, 2023)
Cholesterol is the precursor of all steroid hormones, and the entry of cholesterol into the mitochondria is the rate-limiting step of steroidogenesis. Voltage-dependent anion channel (VDAC1) is an outer mitochondrial protein part of a multiprotein complex that imports cholesterol. We previously reported that intratesticular administration of a 25 amino acid peptide blocking the interaction between 14-3-3ε with VDAC1 increased circulating levels of testosterone. This fusion peptide was composed of a HIV-1 transactivator of transcription (TAT) protein transduction domain cell-penetrating peptide, a glycine linker, and amino acids 159-172 of VDAC1 (TV159-172). Here, we describe the development of a family of small molecules that increase circulating testosterone levels after an oral administration. We first characterized an animal model where TV159-172 was delivered subcutaneously. This subcutaneous model allowed us to study the interactions between TV159-172 and the hypothalamus-pituitary-gonadal axis (HPG) and identify the biologically active core of TV159-172. The core consisted of the tetrapeptide RVTQ, which we used as a platform to design synthetic peptide derivatives that can be administered orally. We developed a second animal model to test various derivatives of RVTQ and found 11 active compounds. Dose-response experiments identified 4 synthetic peptides that robustly increased androgen levels in a specific manner. We selected RdVTQ as the leading VDAC1-core derivative and profiled the response across the lifespan of Brown-Norway rats. In summary, we present the development of a new class of therapeutics that act within the HPG axis to increase testosterone levels specifically. This new class of small molecules self-regulates, preventing abuse.